Health Status and Risk Behaviors of Sexual Minorities Among Chinese Adolescents: A School-Based Survey. Issue 3 (23rd February 2017) - Zhang, Huiping; Wong, William C. W.; Ip, Patrick; Fan, Susan; Yip, Paul S. F.
ABSTRACT: This study aimed to examine the association between sexual orientation and health disparities among a stratified random sample of 3776 secondary students in Hong Kong. The prevalence of homosexuality and bisexuality were 1.5% and 2.6% in boys and 1.8% and 3.7% in girls, respectively. A total of 10.7% of boys and 8.8% of girls were unsure of their sexual orientation. Homosexual and bisexual boys reported poorer physical and mental health than their heterosexual peers. Homosexual and bisexual boys were more likely to engage in smoking, frequent drinking, and vaginal sex and be subjected to sexually transmitted disease and sexual victimization. However, lesbian and bisexual girls were less likely to engage in risky health behaviors except for smoking and being subjected to sexual victimization. There is a gender-specific problem that may warrant prevention and intervention programs to address the unique health issues facing homosexual and bisexual adolescents in Hong Kong.